Possibilities social sphere's government control in the conditions of recurrence of economy - Blahorazumova, Olga (Skhid, 2013)
In the article is examined the role of government control in the development of social sphere. On the basis of theoretical analysis an author examined the problem of correlation of the market and state adjusting of the mixed economy. It is grounded a conclusion about priority of government control of social processes, what be going on in the conditions of modern world and national problems, recurrence of development of economy.